Oil push inflation? - PARKIN, M. (PSL Quarterly Review, 2013)
The present work investigates the “oilpush” view of inflation, its line of reasoning and its conclusions, by examining the evolution of inflation and related variables in six countries, over the period 1968-1978. The paper is mainly empirical, using standard propositions from macroeconomics and monetary theory which are in the background, however, rather than the forefront. The oil push hypothesis is first examined and found to be lacking in empirical content. The monetary policies of the last decade are then reviewed and found to account well for the evolution of inflation. Finally, the costs of the reduction of inflations in the post-1973 period are briefly examined. JEL: E31